Investigation on Flooding-Resistant Performance of Integral Abutment and Jointless Bridge - Yizhou Zhuang; Keyao Wu; Liang Xu; Huihui Li; Diego Maria Barbieri; Zhumei Fu (Advances in Civil Engineering)
Bridge washouts connected to flood events are deemed one of the main reasons for structural collapse. Compared to traditional continuous jointed bridges, integral abutment and jointless bridges (IAJBs) have better lateral stability because there are no expansion devices. The mechanical performance of Shangban IAJ bridge, located in Fujian, China, is thoroughly investigated by Finite Element Analysis (FEA). The numerical model is created and validated based on experimental results obtained from static load tests performed on the bridge. A detailed parametric analysis is carried out to assess the correlation between the flood-resistant performance and a number of parameters: skew angle, water-blocking area, span number, pile section geometry, and abutment height. Except for the abutment height, other parameters significantly affect the bridge performance. Furthermore, the change in the span number has a meaningful impact only when fewer than four spans are modeled. Finally, pushover analyses estimate the maximum transverse displacement and the sequence of plastic hinge creation as well as the mechanical behaviour of the structure under lateral flood loads. The analysis results show that IAJBs have better flooding-resistant performance than conventional jointed bridges.